Consumer Behaviour in the Accommodation Services Market - a Comparison of Vienna, Bratislava and Prague in 2018 - Martin Petrićek; Stepań Chalupa (Comparative Economic Research. Central and Eastern Europe, 2021)
The paper aims to compare three accommodation services markets using empirical data from more than 250 accommodation facilities in specific destinations (Vienna, Bratislava, Prague). The data are available on a daily basis, but the resulting comparison is then performed on a monthly basis within 2018. The comparison is performer based on three basic criteria - occupancy, average daily rate and an indicator of price elasticity of demand. Price elasticity is measured using a log-log regression analysis. The key findings of the comparison are as follows: (1) The Vienna and Prague markets are similar in terms of occupancy and coefficient of price elasticity. In contrast, the Bratislava market showed statistically significant differences from the other two markets in all the criteria under review. (2) The Bratislava market operates at a significantly lower price range compared to the other markets analysed. In the long term, this market has also been lower in the field of occupancy. (3) The markets in Vienna and Prague respond more dynamically to changes in consumer behaviour by changing prices. (4) The so-called "November Phenomenon" has been identified, where all indicators in all markets behave unconventionally. (5) All markets have in common the fact that they have shown price-inelastic demand over the long term, and at the turn of the year, they all face Giffen's paradox.
Keywords: 330; accommodation service; consumer behaviour; price elasticity; Vienna; Bratislava; Prague